RAMAN SPECTROSCOPY ANALYSIS OF CORONARY DENTIN OF VITAL AND ENDODONTICALLY TREATED TEETH - Ekaterina Karteva; Neshka Manchorova; Teodora Karteva; Zhelyazko Damyanov (Peytchinski Publishing, 2022)
PURPOSE: The present study aimed to investigate the properties of coronary dentin of vital and endodontically treated human teeth using Raman Spectroscopy. MATERIAL/METHODS: The samples used were taken from coronary dentin of intact extracted human teeth, ultrasonically cleaned and stored in a 0.2% thymol solution at 4 degrees Celsius for up to 3 months. They were divided into two groups - "vital dentin" and "endodontically treated dentin" samples. Each sample was crossed-sectioned, embedded in resin, polished and subjected to Raman spectroscopy with a Horiba Jobin-Yvon T64000 triple-grating spectrometer, using a CdHe laser with 4 μm diameter of the laser spot and 2.5mW of power on the examined surface. The resultant diagrams were analyzed using the software package Origin 9.6 andunderwent baseline correction and normalization. A comparison between the two studied groups was made. RESULTS: The results from the "vital dentin" group showed a well-expressed crystalline structure, with clear peaks corresponding to pure and b-carbonated hydroxyapatite. The results of the "endodontically treated dentin" group showed the presence of new chemical compounds - octacalcium phosphate, tricalcium phosphate and dicalcium phosphate dihydrate, as well as increased intensity of the b-carbonated hydroxyapatite peaks. CONCLUSIONS: The presence of mineral substances with low calcium content could contribute to a decrease in dentin toughness, which in turn can lessen the mechanical properties of endodontically treated teeth. Raman spectroscopy can be a useful tool in the detection of these dentin components.